Tests of arc lamps - Jacobus, C. R.; Young, S. S. (My University, 1908)
Introduction: In the year 1800 Volta observed the spark, in which year, also, Davy discovered the particularly bright spark between charcoal points separated in air or in liquids, which pressure from 150 elements. In 1808 Davy with a battery of 2000 elements exhibited the first true arc, a flame of about four inches long, before the Royal Institution at London, England.
Citation: Jacobus, C. R. and Young, S. S. Tests of arc lamps. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Electricity; Lamps; Power; Graduating theses; Senior theses; Theses